The Role of AI In Vocational Education: A Systematic Literature Review - Mohamad Iqbal Rosyadi; Iwan Kustiawan; Emmanuel Obobi Tetehfio; Quinera Joshua (Journal of Vocational Education Studies, 2023)
This research aims to comprehensively investigate and explain the important role of Artificial Intelligence (AI) in the field of education, with a particular focus on vocational education. Using the systematic literature review (SLR) method as the chosen research approach, the researchers carefully scrutinized a selection of articles published in the time span between 2018 to 2023, which were carefully selected from the Scopus database. The PRISMA method, renowned for its precision, was carefully applied to screen and filter out documents that did not fit the strict inclusion and exclusion criteria outlined for the study. Upon examination and review of the selected articles, an interesting pattern emerged, underscoring the considerable impact and transformative potential of AI in the education sector, with a particular emphasis on vocational education. The advent of AI technologies has ushered in a new era, one that is brimming with potential to revolutionize and enhance the teaching-learning experience in educational settings. It is quite clear that a thoughtful and strategic implementation of AI promises to improve the efficiency, personalization, and overall effectiveness of education, thus paving the way for a brighter and more adaptive educational landscape.